(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
The article defines the influence of the distance between the feeding rollers and the caustic plank drum on the cleaning effect of machines. As a result of experimental studies, it was achieved on increasing the cleaning effect of machines on the 1-grade 5.0–6.0%, and in the 3-grade 7.0–8.0%